The level of Dentist’s knowledge about emergency management of odontogenic infection: quantitative descriptive - Qalbi, Shafa Aini; Sjamsudin, Endang; Nurwiadh, R. Agus (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Odontogenic infections have been one of the most common diseases in the oral and maxillofacial region. Odontogenic infection is an emergency that must be treated by a dentist immediately because it will cause significant problems. A dentist is a medical practitioner who specializes in the diagnosis and treatment of problem that affect teeth, mouth, and the surrounding maxillofacial structure. Knowledge is needed by dentist to confirm the diagnosis in performing emergency of odontogenic treatment. The purpose of this study was to measure the level of dentists’ knowledge in Bandung hospitals about emergency treatment of odontogenic infections. Methods: This research used a quantitative descriptive method with cluster sampling technique. The study was conducted on 45 general practitioners and 47 specialists who work in Bandung hospitals using an instrument questionnaire with 15 questions. Results: Total of 27 respondents (29.3%) were in the sufficient category and 65 respondents (70,7%) were in a good category. Dentist average encountered cases of odontogenic infection at least once a week, both before the 2019 pandemic and in the last three months, with percentages of 38% and 39,1% respectively. Conclusion: The level of dentists’ knowledge in the city of Bandung hospitals about emergency treatment of odontogenic infections is in a good category. The description of knowledge about management treatment of odontogenic infections in this questionnaire ensures that cases can be handled effectively.KEY WORDS: knowledge, emergency, treatment, odontogenic, infections, hospitalTingkat pengetahuan dokter gigi mengenai perawatan darurat infeksi odontogenABSTRAKPendahuluan: Infeksi odontogen menjadi salah satu penyakit umum yang paling banyak ditemukan di rongga mulut dan maksilofasial. Infeksi odontogen merupakan keadaan darurat yang harus segera ditangani oleh dokter gigi karena akan menimbulkan permasalahan lain secara signifikan. Dokter gigi adalah praktisi medis yang khusus mendiagnosis dan memberikan perawatan pada gigi, mulut, dan maksilofasial di sekitarnya. Pengetahuan yang memadai dibutuhkan dokter gigi untuk menegakkan diagnosis dalam melakukan perawatan darurat infeksi odontogen. Tujuan penelitian mengukur tingkat pengetahuan dokter gigi mengenai perawatan darurat infeksi odontogen. Metode: Jenis penelitian deskriptif kuantitatif dengan teknik pengambilan sampel cluster sampling. Penelitian dilakukan pada 45 dokter gigi umum dan 47 dokter gigi spesialis yang bekerja di rumah sakit Kota Bandung menggunakan instrumen berupa kuesioner dengan 15 butir pertanyaan. Hasil: Sebanyak 27 responden (29,3%) berada pada kategori cukup dan 65 responden (70,7%) berada pada kategori baik. Rata-rata dokter gigi menjumpai kasus infeksi odontogen setidaknya 1x dalam seminggu baik sebelum pandemi 2019, maupun dalam tiga bulan terakhir dengan persentase 38% dan 39,1% Simpulan: Tingkat pengetahuan dokter gigi di rumah sakit Kota Bandung mengenai perawatan darurat infeksi odontogen berada dalam kategori baik. Pengetahuan mengenai manajemen perawatan infeksi odontogen pada kuesioner tersebut memastikan kasus-kasus dapat ditangani secara efektif.KATA KUNCI: pengetahuan, perawatan darurat, infeksi, odontogen, rumah sakit